‘UMAR IBN AL-KHATHTHÂB DAN SIYÂSAH SYAR‘IYYAH - Azhari Akmal Tarigan (State Islamic University North Sumatra, 2008)
Abstract: ‘Umar Ibn al-Kaththâb and Islamic Polity: An experimentation of Application of Islamic Law in Local Context. The compatibility of Islamic teaching to all times and places, in itself, makes ijtihâd indispensable. That is to say that Islamic tenets need to be interpreted in a specific context of time and space. ‘Umar ibn al-Khaththâb has always been regarded as the prototype of such efforts. Many innovations in different aspects of life were accredited to ‘Umar, making him a very popular reference for later generations in performing ijtihâd. This article examines the contribution of ‘Umar’s experimentation with the syari‘ah, providing the readers with some interesting examples. Kata Kunci: ‘Umar Ibn al-Khaththâb, siyasah, had